Erratum: Sukkharak, P. (2017) A revision of the genus Pleurozia (Marchantiophyta: Pleuroziaceae) in Thailand and little known morphological features of the genus. Phytotaxa 309 (3): 201–216. - Sukkharak, Phiangphak (Phytotaxa, 2017)
N/A